Novel bufferless photosynthetic microbial fuel cell (PMFCs) for enhanced electrochemical performance - Wang, Chin Tsan; Huang, Yan Sian; Sangeetha, Thangavel; Chen, Yen Ming; Chong, Wen Tong; Ong, Hwai Chyuan; Zhao, Feng; Yan, Wei Mon (Elsevier, 2018)
Photosynthetic microbial fuel cells (PMFCs) are novel bioelectrochemical transducers that employ microalgae to generate oxygen, organic metabolites and electrons. Conventional PMFCs employ non-eco-friendly membranes, catalysts and phosphate buffer solution. Eliminating the membrane, buffer and catalyst can make the MFC a practical possibility. Therefore, single chambered (SPMFC) were constructed and operated at different recirculation flow rates (0, 40 and 240 ml/min) under bufferless conditions. Furthermore, maximum power density of 4.06 mW/m2, current density of 46.34 mA/m2 and open circuit potential of 0.43 V and low internal resistance of 611.8 Ω were obtained at 40 ml/min. Based on the results it was decided that SPMFC was better for operation at 40 ml/min. Therefore, these findings provided progressive insights for future pilot and industrial scale studies of PMFCs.